The COVID-19 pandemic in Germany - Wu¨stner, Kerstin (Psihološka obzorja (Ljubljana), 2025)
In crises such as the COVID-19 pandemic states, organizations, and individuals try to cope with a variety of challenges. The pandemic caused fear and some individuals felt a need for solidarity and conformity. A crisis such as the pandemic was likely to reinforce authoritarian attitudes. This paper aims to explore how these aspects were perceived during the COVID-19 pandemic and whether they contributed to the desire to punish non-conforming individuals. To this purpose, an online survey was conducted in Germany (n = 285). This study shows that punitive attitudes could be partly explained by expected solidarity, the need for conformity, fear of health damage caused by the COVID-19 virus – and a lack of fear of other consequences of the pandemic, and by authoritarian aggression. Due to the limitations of the small sample, the results can only provide some indications for further research, which are discussed in the conclusion.
Keywords: authoritarianism; avtoritarnost; conformity; COVID-19; interpersonal trust; konformnost; medosebno zaupanje; punitive attitudes; solidarity; solidarnost; stališča do kaznovanja